The effect of pre-exercise glucose ingestion on performance during prolonged swimming - Smith, G. J.; Rhodes, E. C.; Langill, R. H. (International Journal of Sport Nutrition and Exercise Metabolism, 2002)
The purpose of this study was to determine if pre-exercise glucose ingestion would improve distance swimming performance. Additionally, pre-exercise glucose was provided at 2 different feeding intervals to investigate the affects of the timing of administration. Ten male triathletes (X ± SD: age, 29.5 ± 5.0 years; VO 2peak, 48.8 ± 3.2 ml · kg-1 ·min-1) swam 4000 m on 3 occasions following the consumption of either a 10% glucose solution 5 min prior to exercise (G5), a 10% glucose solution 35 min prior to exercise (G35), or a similar volume of placebo (PL). Despite a significant difference (p < .01) in blood glucose concentration prior to exercise (X ± SD in mmol · L-1: G35 8.4 ± 1.1 vs. G5 5.2 ± 0.5 or PL 5.3 ± 0.4), no significant differences were observed in total time (X ± SD in minutes: G35 70.7 ± 7.6, G5 70.1 ± 7.6, PL 71.9 ± 8.4), post-exercise blood glucose (X ± SD in mmol ·L-1: G35 5.1 ± 1.1, G5 5.1 ± 0.9, PL 5.3 ± 0.4), and average heart rate (X ± SD in bpm: G35 155.8± 10.8, G5 153.6 ± 12.6, PL 152.0 ± 12.5; p > .05). While not reaching statistical significance, glucose feedings did result in improved individual performance times, ranging from 24 s to 5 min in 8 of the 10 subjects compared to the placebo. These results were found despite significant differences in blood glucose between trials immediately prior to exercise.